EXAMINATION OF THE INDICTMENT - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In modern criminal procedure after the investigation has been completed and the indictment has been raised, it is necessary that a certain functional form of the court controll and examine the indictment. Before the trial commences, first the indictment is being judged, in sense it has to be determined whether the conditions are met to bring the defendant before the main trial, and whether the entry into the next stage is justified and lawful. In this way, the purpose of the judicial review of the charge is determined in order to prevent the unjustified and unlawful execution of the defendant into the main trial. The subject of this paper is the analysis of the legal regulation of the examination of the indictment in the Criminal Procedure Code, as well as the analysis of the proceedings of the pre-trial court of the High Court in Novi Sad regarding the examination of the indictment.